Nilai-Nilai Pendidikan Islam Dalam Novel Youkoso Jitsuryoku Shijou Shugi no Kyoushitsu e Karya Kinugasa Shougo dan Relevansinya dengan Pendidikan Islam - Fatkhurrohman Al Hudri, Muhammad Avicena; Kusumaningratri, Rose (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This research aims to explore the educational system of the White Room in the novel "Youkoso Jitsuryoku Shijou Shugi no Kyoushitsu e" and its relevance to Islamic education. The type of research conducted is a literature study or library research with a qualitative research approach. The data collection technique used is document content analysis and employs Miles and Huberman's data analysis technique. The research findings indicate that the White Room is an educational institution with a unique concept. It educates and nurtures children from birth to adulthood. The education provided in the White Room can be considered challenging, as many children are expelled from the White Room for not being able to keep up with the learning activities. Nevertheless, there are still some children who successfully undergo education in the White Room with satisfying results. Furthermore, the White Room is relevant to Islamic educational values. The Islamic values practiced in the White Room's education include maintaining health, expressing gratitude, and working hard. Additionally, the moral values taught in the White Room's education involve non-discrimination, a high sense of curiosity, and obedience to teachers.